Classification of segmental vitiligo on the trunk3. (February 2014) - van, N.; Bosma, S.; Boone, B.; Speeckaert, R.
<x xml:space="preserve">Abstract</x> What's already known about this topic? A classification for segmental vitiligo lesions on the face has been reported. Currently, a classification for segmental vitiligo on the trunk is still unavailable. What does this study add? This is the first study providing a classification for segmental vitiligo lesions located on the trunk. This classification will have a prognostic value with respect to the future distribution of early lesions. This information may provide diagnostic clues in doubtful clinical situations.